Implementation of Self Regulated Learning in Online and Offline Physical Education Teaching To Improve The Learning Motivation of Class XII - Reshandi Nugraha; Aden Azza Harsena; Tite Juliantine (Journal of Physical Education For Secondary Schools, 2022)
Introduction: Researchers implement self-regulated learning in teaching physical education online and offline to increase student learning motivation. Purpose: To test the effect of offline and online self- regulated learning, as well as test how the differences in the effect of offline self-regulated learning and online self-regulated learning have on student learning motivation. Methods: This research is a quantitative study using the experimental method. The sampling technique used was purposive sampling with a sample of 72 students in class XII MIPA 1 and XII MIPA 5. Using instruments developed based on aspects of learning motivation Hamzah B, Uno 2009, namely 8 indicators of learning motivation including concentration, curiosity, enthusiasm, independence, readiness, enthusiasm or encouragement, never giving up, and self-confidence. Results: data collection techniques were carried out 2 times, namely by pre-test and post-test.based on the Paired Sample t test on the implementation of self-regulated learning offline with a test level of 0.05, a p-value of 0.873 is obtained so that H0 is accepted, test level Paired Sample t Test on the implementation of online self-regulated learningof 0.05 obtained a p-value of 0.007 so that it rejects H0. Test whether there are differences in the effect of offline self-regulated learning and online self-regulated learning z-count is -1.066, the results of the analysis of the Mann-Whitney u test or Sig (2-tailed) are 0.266 probability value 0.05, so H0 is accepted.Based on confidence intervals with a 95% confidence level and a sample size of 72. Conclusions: 1). The implementation of self-regulated learning in offline physical education teaching did not change or there was no increase in the pretest- posttest results, which means that there was no increase in learning motivation. 2). The implementation of self-regulated learning in online physical education has experienced or there has been an increase in pretest-posttest results so that it can be interpreted as experiencing an increase in learning motivation. 3). comparison of differences in learning motivation between online and offline through the implementation of self-regulated learning is said to be the sameÂ